Odors in Cognitive Research: a commentary on 'Scented Colours' and an evaluation study on odor quality, with the example of human wayfinding - Kai Hamburger; Denise Herold (Baltic International Yearbook of Cognition, Logic and Communication, 2021)
In his target article on “Scented Colours”, Charles Spence highlights the importance of crossmodal connections by focusing on the interaction between odors and colors. In this commentary and our presentation of own empirical work in this research context, we want to reach out further by emphasizing this importance not only on a perceptual and representational level, but also highlight it as an example for spatial cognition research. We provide an evaluation study on emotional effects of odors that could be used in future interdisciplinary research. While the meaning of odors in spatial wayfinding is, thus far, not well investigated, we want to briefly introduce the current research state, focus on new and valuable research strains in this area as an example for the importance of odors in cognitive research.
Keywords: crossmodality; way-finding; perception